Preparedness in Implementing Merdeka Curriculum: Insights from Indonesian EFL Teachers - Nuranisa (Universitas Cokroaminoto Palopo, 2024)
This research examines the preparedness of Indonesian English as a Foreign Language (EFL) instructors to implement the Merdeka Curriculum. It focuses on six indicator areas: adapting to change, teacher's ability to adapt learning strategies to student needs, teacher skills in involving students in active and creative learning, supporting resources, institutional support, and professionalism enhancement. Through a phenomenological case study, four EFL teachers in Indonesia share their insights and experiences in integrating the new curriculum into their teaching. The results reveal that teachers value adaptability and recognize the benefits of the Merdeka Curriculum in addressing individual student needs. They employ diverse teaching methods to promote student engagement and participation. Schools offer sufficient technological and institutional support, including training and resources, to facilitate effective curriculum implementation. Nonetheless, instructors express the importance of ongoing professional growth to tackle challenges and enhance readiness. In summary, the study concludes that Indonesian EFL instructors are ready and receptive to implementing the Merdeka Curriculum, underscoring the significance of continual learning and innovation in education.